Neuroprotective effects of Daphnetin on hippocampal neurons and blood-brain barrier integrity in a mouse model of cerebral ischemia - Maysam Havasi Mehr; Shahein Momenabadi; Ali Vakili; Abbas Pakdel; Abbas Ali Vafaei; Abedin Vakili (Brain Research Bulletin, 2024)
The purpose of this research was to assess the impact of different doses of Daphnetin (DAP, a natural compound derived from coumarin) on hippocampus neuronal injury, neurobehavioral function, blood-brain barrier (BBB) integrity, expression of claudin-5, brain-derived neurotrophic factor (BDNF), superoxide dismutase (SOD), and inflammatory markers in a mouse model of cerebral ischemia. Cerebral ischemia was induced in mice through 30 minutes of bilateral common carotid occlusion (BCCAO), followed by 48 hours of reperfusion. The viability of hippocampal neurons was assessed using Cresyl violet staining and BBB function was determined by measuring Evans blue (E.B) dye leakage. Spatial memory was tested using the Radial Arm Water Maze (RAWM) task. Claudin-5 and BDNF were measured by immunofluorescence, while SOD, interleukin-1 beta (IL-1β), and nuclear factor-κB (NF-κB) expression were determined through western blotting. Administering DAP significantly increased neuron survival in the hippocampus CA1, CA3, and dentate gyrus (DG) regions and improved spatial memory dose-dependently (P<0.0001). Treatment with DAP (40 mg/kg IP) significantly reduced E.B leakage and brain water content (P<0.001). Furthermore, it increased the claudin-5, BDNF, and SOD levels and diminished NF-κB and IL-1β expression (P<0.0001). The research found that DAP protected neurons in the CA1, CA3, and DG areas of the hippocampus, enhanced behavioral functions, and preserved BBB integrity in a cerebral ischemia model. This positive impact is achieved by increasing the expression of claudin-5, BDNF, and SOD and diminishing neuroinflammation. Further research is required to clarify the mechanisms and possible clinical uses.